Understanding of mental fatigue in elite fencing sports: perspectives from Chinese national level fencers - Bian, C.; Russell, S.; De Pauw, K.; Habay, J.; Bogataj, Š.; Roelands, B. (Frontiers in Psychology, 2025)
Introduction: Recent studies have documented the presence, fluctuation, and persistence of mental fatigue (MF) across various elite sports. It appears that open-skilled competitive contexts tend to impose greater mental demands, leading to higher levels of MF. Fencing, as an open-skilled combat sport, requires perceptual-cognitive skills and mental resources allocation for an optimal performance. However, it is underrepresented in the MF research domain.